From Utopian One-worldism to Geopolitical Intergovernmentalism - Per Wisselgren (Royal Danish Library, 2017)
As a new coordinating organization in the rapidly expanding international field of post-World War II social science, UNESCO’s Department of Social Sciences (SSD), set up in 1946, played a central role. This article explores the formation of the SSD during its first decade with a special focus on its organizational aspects. By conceptualizing the SSD as an “international boundary organization”, the article analyzes the organizational structuration of agency spaces on different levels – within SSD, in relation to UNESCO and to the UN system at large – as well as over time. As a result, the article discerns four phases, distinguished by organizational changes, under which the SSD was successively transformed from a relatively independent transnational organization, which shared the utopian vision of one-worldism, to an intergovernmental organization considerably more vulnerable to external geopolitical pressures.